Astragalin Suppresses Inflammatory Responses and Bone Destruction in Mice With Collagen-Induced Arthritis and in Human Fibroblast-Like Synoviocytes - Jia, Qingyun; Wang, Tengteng; Wang, Xiaoyun; Xu, Hao; Liu, Yang; Wang, Yongjun; Shi, Qi; Liang, Qianqian (Frontiers in Pharmacology, 2019)
Astragalin, a bioactive flavonoid with anti-inflammatory, antioxidant, and protective properties, is a potential agent for the treatment of rheumatoid arthritis (RA). In this study, the mechanisms underlying the therapeutic efficacy of astragalin in the treatment of RA were analyzed using DBA/1J mice with collagen-induced arthritis (CIA) and fibroblast-like synoviocytes derived from RA patients (MH7A cells). We demonstrated that astragalin significantly attenuated the severity of arthritis in CIA mice. The therapeutic eﬀects were associated with decreased the severity of the arthritis (based on the arthritis index), joint swelling and reduced bone erosion and destruction. Furthermore, Astragalin treatment suppressed the production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-8), and inhibited the expression of matrix metalloproteinases (MMP-1, MMP-3 and MMP-13) in chondrocytes and synovial cells of CIA mice. In vitro, astragalin also inhibited the expression of matrix metalloproteinases (MMP-1, MMP-3 and MMP-13) in TNF-α-induced MH7A cells in a dose-dependent manner and with no apparent cytotoxicity. Also, astragalin suppressed the phosphorylation of p38, JNK, and the activation of c-Jun/AP-1 in TNF-α-induced MH7A cells. In conclusion, this study proved that astragalin could attenuate synovial inflammation and joint destruction in RA at least partially by blocking the phosphorylation of MAPKs and the activation of c-Jun/AP-1. Therefore, astragalin can be a potential therapeutic agent for RA.